The Effect of Group Investigation Learning Model on Science Education Students’ Mastery of Environmental Pollution and Creative Thinking - Nestiadi, Adi (Jurnal Pendidikan Indonesia Gemilang, 2024)
The learning process in the classroom still tend to focus on the teacher, causing less students are actively involved in the learning process seen in the number of students who ask and answer questions that lead to low test score is below standard. Application of group investigation learning model was expected to improve the mastery of concepts and creative thinking of students. This research aimed to determine the influence of the learning model group investigation to the mastery of concept environment pollution  and creative thinking in high school student of class X. The research method used was quasi-experimental with the research design post-test control group design. The research sample of 60 students was 30 students each in the experimental class and control class by simple random sampling. The instrument used was the test the ability of mastering concept and creative thinking test. based on the analysis the data were normally distributed and homogeneous. The result of this reseach 1). There an influence of learning model group investigation of the mastery of concept inveronment pollution and creative thinking student 2). Mastery of concepts students using learning model group investigation to get a better score than the students who use STAD learning model with value (tcount = 4,118) 3). Creative thinking abilities of students using learning model group investigation to get a better score than the students who using learning model STAD with value (tcount = 2.731).